2018
DOI: 10.18203/2394-6040.ijcmph20183097
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of antenatal care and out of pocket expenditure on delivery care in Dakshina Kannada

Abstract: Background: Maternal health refers to the health of women during pregnancy, childbirth and the postpartum period. Factors like education, economic status and out of pocket (OOP) expenditure can affect utilization of maternal health services. Hence this study aims to assess the utilization pattern of maternal health care and the out of pocket expenditure for delivery services in a public maternity hospital. Methods: A cross sectional study was conducted using primary data from women who delivered in public mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 9 publications
4
17
1
1
Order By: Relevance
“…The median OOP expenditure for child delivery care in India was INR 1000 ($15.6) with an average cost of INR 5985 ($93.3). This finding was similar to some of the small‐scale studies conducted in various parts of India like Odisha (INR 1100), Mangalore (INR 1150), and Lucknow (INR 1406) . However, a previous large‐scale survey conducted in India (District Level Household Survey‐3) showed significantly lesser OOP expenses ($44) for delivery services when compared with the current study findings .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The median OOP expenditure for child delivery care in India was INR 1000 ($15.6) with an average cost of INR 5985 ($93.3). This finding was similar to some of the small‐scale studies conducted in various parts of India like Odisha (INR 1100), Mangalore (INR 1150), and Lucknow (INR 1406) . However, a previous large‐scale survey conducted in India (District Level Household Survey‐3) showed significantly lesser OOP expenses ($44) for delivery services when compared with the current study findings .…”
Section: Discussionsupporting
confidence: 89%
“…Only 36.4% of mothers utilized the JSY scheme . Although several small scale studies have been conducted to determine OOP expenditure on health, little information is available on the cost incurred for maternal health services and its determinants at the national level . Hence, this study aims at finding the costs incurred for child delivery care and determinants of OOP payments made toward the same in India.…”
Section: Introductionmentioning
confidence: 99%
“…Current study revealed that 91.5% had the minimum 4 antenatal visits, similarly, Tellis SB et al, found that 97.3% had the minimum number of visits. 13 Adequate IFA supplementation was received by 83.1% of the women in this study, which was similar to the other study in the district (82.2% consumed all the IFA tablets). 13 Also a study by Pai DV et al, reported, IFA consumption as 85.6% at udupi.…”
Section: Discussionsupporting
confidence: 87%
“…13 Adequate IFA supplementation was received by 83.1% of the women in this study, which was similar to the other study in the district (82.2% consumed all the IFA tablets). 13 Also a study by Pai DV et al, reported, IFA consumption as 85.6% at udupi. 14 Injection TT coverage was 98.6% in this study and 99% received Injection TT in Tellis SB et al, study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation